Verfremdete Erfahrung - Waldenfels, Bernhard (B@belonline, 2020)
The question of the alien is certainly not a very frequent problem in the philosophical tradition, even if it has often appeared in the most diverse contexts. With Husserl and the phenomenological tradition, experience was also investigated according to its failures, where, for instance, something shows itself by hiding. This strangeness is a kind of absence in flesh and blood, a distance in proximity, the accessibility of what remains inaccessible, as Husserl pointed out in his Cartesian Meditations. But how to deal with all this without depriving it of its sting? We have not to discuss about a question, but to get started from a hitch, looking for answers, in the awareness that our pathos starts in any case from elsewhere. Thus the human being turns out to be a homo respondens.